2022
DOI: 10.3389/fpls.2021.779302
|View full text |Cite
|
Sign up to set email alerts
|

Peanut Rotation and Flooding Induce Rhizobacteriome Variation With Opposing Influences on the Growth and Medicinal Yield of Corydalis yanhusuo

Abstract: Corydalis yanhusuo, a precious herb of the Papaveraceae family, is widely used in multiple traditional Chinese medicines for the treatment of many painful conditions, and its medicinal part is the dried tuber. Yet how to improve this plant’s medicinal yield as well as its economic efficiency remains a key problem in its cultivation. The planting of C. yanhusuo in rotation with peanut (Arachis hypogaea L.) aims to improve land utilization efficiency, but the total production of tubers is severely reduced relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 66 publications
0
8
0
Order By: Relevance
“…mongholicus (Bge.) Hsiao (Huangqi in Chinese) ( Li et al, 2021 , Li et al, 2021 , Li et al, 2021 , Li et al, 2021 ), Sophora flavescens Ait. (Kushen in Chinese) ( Lei, Liu, Zhao, Hou, & Wang, 2020 ), P. ginseng ( Tong, Liu, Liu, Xia, & Zhu, 2021 ), Cut Chrysanthemum ( Wang et al, 2022 , Wang et al, 2022 , Wang et al, 2022 , Wang et al, 2022 , Wang et al, 2022 ) and other rhizosphere bacteria showed a decayed pattern with time under the influence of culture year, while the pathogenic fungal communities were enriched.…”
Section: Research Foundation Of New Concept “Micro-markers”mentioning
confidence: 99%
See 3 more Smart Citations
“…mongholicus (Bge.) Hsiao (Huangqi in Chinese) ( Li et al, 2021 , Li et al, 2021 , Li et al, 2021 , Li et al, 2021 ), Sophora flavescens Ait. (Kushen in Chinese) ( Lei, Liu, Zhao, Hou, & Wang, 2020 ), P. ginseng ( Tong, Liu, Liu, Xia, & Zhu, 2021 ), Cut Chrysanthemum ( Wang et al, 2022 , Wang et al, 2022 , Wang et al, 2022 , Wang et al, 2022 , Wang et al, 2022 ) and other rhizosphere bacteria showed a decayed pattern with time under the influence of culture year, while the pathogenic fungal communities were enriched.…”
Section: Research Foundation Of New Concept “Micro-markers”mentioning
confidence: 99%
“…Stenotrophomonas enrichment in the A. membranaceus rhizosphere can produce substances that regulate plant growth and promote the accumulation of bioactive ingredients, thereby promoting the growth of A. membranaceus and secretion of metabolites. The root exudates can in turn support the growth of Stenotrophomonas in the rhizosphere, thereby increasing the content of astragaloside ( Li et al, 2021 , Li et al, 2021 , Li et al, 2021 , Li et al, 2021 ).…”
Section: Research Foundation Of New Concept “Micro-markers”mentioning
confidence: 99%
See 2 more Smart Citations
“…These results demonstrated a large difference in the accumulations of 13 marker compounds (peaks 13,5,6,10,26,21,16,20,23,22,14,19,8) in different origins. We also analyzed the 16 marker compounds (peaks 22,27,19,7,12,21,5,26,9,4,1,28,8,6,24,17) in CR from different storage time and kneading processing (Figure 9B). The contents of the 16 marker compounds were extremely high in K0Y samples, indicating that CR was of good quality after kneading.…”
Section: Determination Of Lobetyolin In Codonopsis Radix Samplesmentioning
confidence: 99%